Capacity and Site Readiness for Hypertension Control Program Implementation in the Federal Capital Territory of Nigeria: A Cross‐Sectional Study. (20th August 2020) - Baldridge, A.; Orji, A.; Omitiran, K.; Guo, M.; Ajisegiri, S.; Ojo, T.; Kandula, N.; Hirschhorn, L.; Huffman, M.; Ojji, D.
Abstract : Research Objective: The prevalence of hypertension among adults in Nigeria is high (29‐45%), yet awareness (14‐30%), treatment (<20%), and control (9%) rates are low. The Hypertension Treatment in Nigeria study aims to improve awareness, treatment, and control of hypertension in Nigeria through adaptation, implementation, and evaluation of a system‐level hypertension control program based on the World Health Organization's (WHO) HEARTs package. Study Design: We performed facility‐based capacity and readiness assessments to inform our implementation and adaptation strategies and research plan at public primary health centers (PHCs) by adapting the WHO's Service Availability and Readiness Assessment (SARA). SARA assessments were performed by interviewing the highest‐level site staff, pharmacists, and laboratory technicians at each PHC. Capacity and readiness assessments were based on staffing levels, availability of key steps in hypertension treatment cascade, equipment and supplies, information system infrastructure, and availability of blood pressure (BP)‐lowering medicines. Population Studied: Among 243 public PHCs within 6 council areas and 62 wards in the Federal Capital Territory of Nigeria, we selected 60 PHCs through a multistage sampling frame. SARA assessments were completed by the research team between May 2019 and October 2019 at all (n = 60; 100%) PHCs. Principal Findings: Most PHCs (n = 54; 90%) had sufficient human resource capacity based on self‐report of two or more full‐time staff. The median (interquartile range [IQR]) number of full‐time staff was 5 (3‐8), predominantly comprised of community health extension workers (median 3; IQR 2‐5) and nurses (median 1; IQR 0‐2). Few (n = 8; 15%) sites received any training for diagnosis and management of cardiovascular diseases within the previous two years. All (n = 60; 100%) sites had sufficient capacity for screening and most for diagnosis (n = 56; 93%) and confirmation (n = 53; 88%) of hypertension. Nearly two‐thirds had capacity for dispensing initial (n = 35; 58%) or follow‐up (n = 37; 62%) BP‐lowering medication and for providing long‐term continued care (n = 38; 63%) for patients with hypertension. Few PHCs had guidelines (n = 7; 13%), treatment algorithms (n = 3; 5%), or information materials (n = 1; 2%) for hypertension diagnosis or management. Most sites (n = 55; 92%) had at least one functional BP apparatus. All sites relied on paper based records, and relatively few had a functional computer (n = 10; 17%) or access to Internet or email (n = 5; 8%). Calcium channel blockers (n = 19 PHCs; 32%) were the most prevalently stocked BP‐lowering medication, followed by central acting agents (n = 11; 19%) and angiotensin‐converting enzyme inhibitors (n = 10; 17%). Despite inclusion on the WHO and Nigeria essential medicines lists, the median (IQR) number of 30‐day treatment regimens of all BP‐lowering medications in stock on the day of assessment was 0 (0‐20) and 35 (59%). PHCs had no BP‐lowering medication in stock. Conclusions: We demonstrated feasibility of implementation based on workforce, equipment, and information systems. Implications for Policy or Practice: This study was the first systematic assessment of capacity and readiness for a system‐level hypertension control program within the Federal Capital Territory of Nigeria. The results demonstrate a critical need for essential medicine supply strengthening, health worker training, and protocols for hypertension treatment and control rates in Nigeria. Primary Funding Source: National Institutes of Health.